Variation of Carrying Angle With Age, Sex, Height and Special Reference to Side - Sharma, K; Mansur, DI; Khanal, K; Haque, MK (Kathmandu University Medical Journal, 2015)
Background The carrying angle is defined as the acute angle made by the median axis of arm and median axis of forearm in full extension and supination. This angle permits the forearms to clear the hips in swinging movements during walking and is important when carrying objects.Objective The purpose of this study was to determine the values of carrying angle in both the sexes according to the age group in relation with height and special reference to side.Methods To evaluate the elbow carrying angle in normal children between 5-15 years by a manual goniometer, measurements were performed in 532 children (Male- 335, Female- 197), with the elbow in full extension and forearm in supination. Carrying angle was measured on right and left upper limbs to find out the difference on both the limbs. Their height, ages and sexes are also recorded. Bicipital groove, biceps brachii tendon at its insertion and palmaris longus tendon at the wrist were palpated and marked as anatomical landmarks to demarcate the median axes of arm and forearm respectively.Results The mean carrying angle of male on the left limb was 7.0359O and the female was 7.8030O and the mean carrying angle of male on the right limb was 4.5509O and the female was 4.9545O. We observed the greater carrying angle in non-dominant limb than the dominant limbs. There was significant positive correlation between height of students and carrying angle left (r =0.0866, p= 0.0480.05).Conclusion The present study showed that the carrying angle was greater in female than in male and was greater in non-dominant arm than in dominant arm and the carrying angle was not inversely related to the height of the person.Kathmandu Univ Med J 2013; 11(4): 315-318